Overexpression of GαS in Murine Osteoblasts In Vivo Leads to Increased Bone Mass and Decreased Bone Quality. (10th August 2017) - Zhang, Lucia; Sugamori, Kim S; Claridge, Colin; dela Cruz, Ariana; Grynpas, Marc D; Mitchell, Jane
ABSTRACT: GαS is a heterotrimeric G protein that transduces signals from activated G protein‐coupled receptors on the cell surface to stimulate adenylyl cyclase/cyclic adenosine monophosphate (AMP) signaling. GαS plays a central role in mediating numerous growth and maintenance processes including osteogenesis and bone turnover. Decreased GαS expression or activating mutations in GαS both affect bone, suggesting that modulating GαS protein levels may be important for bone health and development. To examine the effects of increased osteoblastic GαS expression on bone development in vivo, we generated transgenic mice with GαS overexpression in osteoblasts (HOM‐Gs mice) driven by the 3.6‐kilobase (kb) Col1A1 promoter. Both male and female HOM‐Gs mice exhibit increased bone turnover with overactive osteoblasts and osteoclasts, resulting in a high bone mass phenotype with significantly reduced bone quality. At 9 weeks of age, HOM‐Gs mice have increased trabecular number, volumetric BMD (vBMD), and bone volume; however, the bone was woven and disorganized. There was also increased cortical bone volume despite an overall reduction in size in HOM‐Gs mice along with increased cortical porosity and brittleness. The skeletal phenotype of HOM‐Gs mice progressed into maturity at 26 weeks of age with further accrual of trabecular bone, whereas WT mice lost trabecular bone at this age. Although cortical bone volume and geometry were similar between mature HOM‐Gs and WT mice, increased porosity persisted and the bone was weaker. At the cellular level, these alterations were mediated by an increase in bone resorption by osteoclasts and an overwhelmingly higher increase in bone formation by osteoblasts. In summary, our findings demonstrate that high osteoblastic GαS expression results in aberrant skeletal development in which bone production is favored at the cost of bone quality. © 2017 American Society for Bone and Mineral Research.